The 2001 Uprising of the Masses in Bizarra by Rafael Spregelburd - Di Pietro, Luciano Fabricio (Universidad Pedagógica y Tecnológica de Colombia, 2018)
In the year 2003 the playwright and director Rafael Spregelburd stages Bizarra, a comedy about the Argentine crisis of 2001. This is the first theater-novel in history, that is to say, a play consisting of 10 chapters; in order to watch it complete, it is necessary to go ten times to the theater. For years, Spre - gelburd has been considered a postmodern author by several academic literary critics as well as by the dramaturgs of the 1960s generation. This article aims at questioning this classification based on the fact that the author has different points of view and practices in common with political theater.